Omnichannel Marketing: Connecting Consumer Experiences from Online to Offline - Ismail Razak (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2023)
Omnichannel marketing is a strategic approach that integrates all distribution channels and customer interactions, creating a consistent and seamless experience from online to offline platforms. This research aims to explore how omnichannel marketing can effectively connect consumer experiences from the online to the offline world. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of omnichannel marketing has had a positive impact in connecting customer experiences from online to offline channels. Customer data integration enables a better understanding of customer preferences and behavior, enabling more targeted marketing strategies. Flexibility in payment systems and omnichannel performance analysis capabilities provide valuable insights for companies to improve the effectiveness of marketing campaigns. Overall, omnichannel marketing proves that continuous customer engagement, personalization of experiences, and channel integration can increase customer satisfaction and support a company's business goals.